THE STAND OF SOCIAL RESPONSIBILITY WITHIN THE STRATEGY OF BUSINESS ORGANIZATION - Drūteikienė, Greta; Seiliūtė, Jovita (Ekonomika, 2009)
The article reviews the essence and the main principles of the strategic management, discusses the strengths and weaknesses that may be caused by the strategy of the organization. The content and the concept of the social responsibility of a business organization is dissertated mainly through the wide elaboration of the argument for and against business organizations to bear and implement the social responsibility. The links between the strategy and the social responsibility have been uncovered by merging the theories and various aspects of the strategic management and the social responsibility as well as the importance of the integration of the element of social responsibility into the strategy of the business organization is revealed. The most recent t models of the formation of organizational strategy, in which the element of the social responsibility as well as the ethic and moral principles may be detected, are presented. Eventually the measurement and assessment problems of the implementation of social responsibility within the framework of organizational strategy are thoroughly discussed.